Development of Teaching and Learning Materials (TLM) For Islamic Schools in Kenya: What Islamic Universities Can Do - Sheikh, Adan Saman (IIUM Journal of Educational Studies, 2016)
This paper attempts to reveal how the Islamic schools in Kenya are beset by absence of relevant teaching and learning materials and the role Islamic universities can play to provide these materials. Madrasa in Kenya have played pivotal role in producing ulama and teachers of religion for more than a century before the advent of Western education on the shores of East Africa. Islamic Integrated schools on the other hand are recent phenomena that arose to mitigate the challenges posed by Western style education that leaves learners with no time to learn based Islamic sciences. The schools combine both the national secular curriculum and Islamic studies. While the national curriculum subjects have adequate teaching and learning materials developed by the Ministry of Education, the Islamic studies section of the schools face serious shortages of relevant textbooks that are aligned with the target curriculum. Different schools use different textbooks including some that were developed in countries such as Saudi Arabia, Eqypt, Yemen and Sudan. This paper argues that the absence of sufficient, curriculum specific teaching and learning resources in Islamic studies is constraining learning thus contributing to poor performance of students in the subjects. The study utilized qualitative approach to gather views across section of participants involved in Islamic education, on the quality and availability of relevant curriculum support materials and the role played by Islamic Universities in bridging the gap in the development and provision of these materials. Interviews, FGD, observation, and documentary analysis were used to collect data from students, teachers, head teachers, and MoE officials.